Diagnostic Reference Levels (DRLs) for SPECT Examinations at the Nuclear Medicine Installation of the RSUD A.W. Sjahranie Samarinda - Nadia Rudyanti; Rahmawati Munir; Erlinda Ratnasari Putri (BULETIN FISIKA, 2025)
Diagnostic reference Level (DRL) is an investigational tool used to help optimize patient protection during diagnostic and interventional procedures in nuclear medicine, the administered activity is based on the patient's body weight. This study aims to determine the diagnostic reference levels (DRLs) for SPECT Examinations: Bone Scan using radiopharmaceutical 99mTc MDP, Whole Body Scan using radiopharmaceutical 99mTc MIBI, and Thyroid Whole-Body Scan using radiopharmaceutical 131I. This study included patient aged 15 to 60 years with body weight ranging 35 to100 kg. The DRL was calculated based on the 75th percentile and the results were compared with the BAPETEN DRL and previous research. Finding. The DRLs determined for RSUD AWS Samarinda were 999MBq for Bone Scan examination using 99mTc MDP, 921.3 MBq for Whole Body Scan using 99mTc MIBI and 3145 MBq for Thyroid Whole-Body Scan. Based on results, the DRL of Bone Scan and Thyroid WBS exceed the BAPETEN DRL while the DRL for Whole Body Scan using 99TC-MIBI is below the BAPETEN DRL.